Shifting Goalposts: Setting Restoration Targets for Waterbirds in the Murray-Darling Basin Under Climate Change - Bino, Gilad; Brandis, Kate; Kingsford, Richard T.; Porter, John (Frontiers in Environmental Science, 2021)
The Murray-Darling Basin (the Basin) is the largest river system in Australia, supplying about 40% of the country’s irrigated agricultural output. Associated water resource development has come with a heavy price for the Basin’s freshwater ecosystems degrading them over decades. Australian governments are attempting to achieve restore environmental sustainability by returning water to the environment through buy-back of irrigation licences and improved water efficiencies. To determine effectiveness, basin-wide management objectives were established for key indicators, including waterbird populations and life histories which can effectively indicate ecosystem function and condition, driven by flow and flooding regimes. Ongoing monitoring of waterbird numbers continues to indicate continued declines. We evaluated feasibility of meeting established waterbird objectives under existing and predicted climates. We modelled long-term waterbird numbers using one of the world’s largest ongoing waterbird surveys (1983-2020), covering about 13.5% of the area of the entire Basin. Our findings suggest that under near future climate change projections, waterbird numbers will likely continue to decline, and remain below restoration targets set for the Basin. We discuss the current policy settings for using environmental water to support waterbird populations, recommending adjustments to restore the Basin’s waterbird populations and their wetland habitats, to meet Australia’s conservation targets in relation to the ongoing global crisis of biodiversity loss.